PENGEMBANGAN MODEL LATIHAN PASSING DALAM PERMAINAN BOLA TANGAN - Ramadan, Gilang (Journal of Sport Science and Education, 2018)
This research and development aim to develop the model of hand ball handling practice. This study begins with a needs analysis with survey method and then develops a hand ball handling model with characteristics in accordance with the results of needs analysis. The development of this exercise model produces a product of a hand-balled passing practice model in accordance with the needs and conformity with the handball playing pattern. The research method used is research and development method with development steps designed by Borg and Gall. Of course, the method is modified by researchers according to the needs of the study. Are 30 physical health and recreation students who have received  handmade hand-ball training subjects before. Based on the data needs analysis results obtained that 100% of students need the development of the source of this hand ball training model. Meanwhile, according to the first expert of hand-ball training model, it?s obtained average score of 3.55 (very good) with a percentage of 88.38%, according of second expert obtained an average score of 3.79 (very good) with a percentage of 89.44%, the lecture of hand-ball training obtained an average score of 3.75 (very good) with a percentage of 93. 75%. The results of small group testing obtained an average score of 3.25 (good) with a percentage of 81.09%, while the results of large group trials obtained an average score of 3.66 (very good) with the percentage of 86.96%